Independent Study Practices in Higher Education Seen from the "Bourdieu" Approach - Vera, Nawiroh (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to analyze the practice of independent learning in tertiary institutions using the "Bourdieu" approach. This approach refers to social theory from Pierre Bourdieu who argues that social practice, including learning practice, is influenced by social, cultural, and economic factors. The research method used is the library research method, which is research that utilizes library resources to obtain research data. And observation of independent learning practices. Data analysis was carried out using key concepts from Bourdieu's theory, such as cultural capital, social capital, and habitus. The results of the study show that independent learning practices in tertiary institutions are influenced by factors such as social background, cultural knowledge, and social networks. Students who have access to higher levels of cultural capital, such as prior education, family knowledge, and economic resources, tend to have better self-learning practices. The findings of this study also indicate that individual habitus plays an important role in self-learning practices. Students who are accustomed to active and independent learning practices early in their lives tend to continue these practices in Univesity.